2020
DOI: 10.1016/j.antiviral.2019.104646
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive bioluminescence imaging of HCoV-OC43 infection and therapy in the central nervous system of live mice

Abstract: Human coronaviruses (HCoVs) are important pathogens that cause upper respiratory tract infections and have neuroinvasive abilities; however, little is known about the dynamic infection process of CoVs in vivo, and there are currently no specific antiviral drugs to prevent or treat HCoV infection. Here, we verified the replication ability and pathogenicity of a reporter HCoV-OC43 strain expressing Renilla luciferase (Rluc; rOC43-ns2DelRluc) in mice with different genetic backgrounds (C57BL/6 and BALB/c). Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 57 publications
0
30
0
4
Order By: Relevance
“…These results, together with data harvested with the use of microfluidic devices (Xona microfluidic), helped to elaborate a putative model of propagation adapted from Tomishima and Enquist [291], in which infectious HCoV-OC43 could either be assembled in the cell body or at different points along the axon using the anterograde axonal transport to propagate between neurons or from neurons to glial cells surrounding neurons in the CNS (Figure 2). Furthermore, based on previous data using different mutant recombinant viruses harboring mutation in the S protein [266,268,269] and making use of a luciferase expressing recombinant HCoV-OC43 [292][293][294], we are now showing that the rate and success of virus propagation towards the spinal cord, in part through the neuron-to-neuron pathway, correlates with the exacerbation of neurovirulence (Figure 3). [269] and adapted from Tomishima and Enquist [291].…”
Section: Human Coronaviruses In the Cns: Possible Associated Neurologmentioning
confidence: 67%
“…These results, together with data harvested with the use of microfluidic devices (Xona microfluidic), helped to elaborate a putative model of propagation adapted from Tomishima and Enquist [291], in which infectious HCoV-OC43 could either be assembled in the cell body or at different points along the axon using the anterograde axonal transport to propagate between neurons or from neurons to glial cells surrounding neurons in the CNS (Figure 2). Furthermore, based on previous data using different mutant recombinant viruses harboring mutation in the S protein [266,268,269] and making use of a luciferase expressing recombinant HCoV-OC43 [292][293][294], we are now showing that the rate and success of virus propagation towards the spinal cord, in part through the neuron-to-neuron pathway, correlates with the exacerbation of neurovirulence (Figure 3). [269] and adapted from Tomishima and Enquist [291].…”
Section: Human Coronaviruses In the Cns: Possible Associated Neurologmentioning
confidence: 67%
“…Data from clinical and animal studies have shown that CoVs can cross the blood-brain barrier (BBB) and exert neuroinvasive properties (Cabirac et al 1994;Cavanagh 2005;Desforges et al 2013;Li et al 2016b;Niu et al 2020;Talbot et al 2011;). The precise mechanisms of penetration into the CNS have not been fully understood.…”
Section: How Can Covs Enter the Cns?mentioning
confidence: 99%
“…[2] Of these, SARS-CoV-1, MERS-CoV, HCoV-OC43, and HCoV-229E are associated with neurological complications. [3] Large territory stroke, polyneuropathy, myopathy, seizures and status epilepticus were reported in patients with SARS CoV-1 outbreak in 2002/2003. [4,5] In-vivo, intranasal inoculation of the SARS-CoV-1 led to severe neuronal loss at the brainstem and speci cally the respiratory center at the medulla.…”
Section: Introductionmentioning
confidence: 99%